Students Instrumental Motivation: An Investigating toward English Learning of Students in Islamic Higher Education - Kholid, Idham; Supriyadi, Supriyadi (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study attempts to explore the profile of instrumental motivation of Universitas Islam Negeri (UIN) Raden Intan Lampung students; comparing instrumental motivation of students of English and non-English major. The design of this research is descriptive qualitative. The survey is conducted to 145 students of English major and 784 students of non-English major as a sample. Questionnaire and interview were employed to collect the data. Research result reveals that students of English major have higher instrumental motivation compared to the students of non-English major, especially related to their future expected job. Interestingly, this study found that differences in motivation between students of English and non-English major arise due to the students' differences orientation on their interest in English. Expecting to acquire a job requiring them to use English, students of English major were likely to possess a higher interest in learning the language. Conversely, students of non-English major do not think that they need English for their prospective job. Therefore, the students of non-English major tend to think that English doesn't support their future careers too much. The findings of this study indicate that for many UIN Raden Intan Lampung students, English is not considered as a useful instrument for their academic activities. The student perspective of English is still segmented.